Austerity, welfare and work : exploring politics, geographies and inequalities / David Etherington. - Etherington, David (Policy Press, 2020)
David Etherington provides bold and fresh perspectives on the link between welfare policy and employment relations as he assesses their fundamental impact on social inequalities. Exploring how reforms, including Universal Credit, have reinforced employment and social insecurity, he assesses the role of NGOs, trade unions and policymakers in challenging this increasingly work-focused welfare agenda. Drawing on international and national case studies, the book reviews developments, including rising job insecurity, low pay and geographical inequalities, considered integral to neoliberal approaches to social spending. Etherington sets out the possibilities and challenges of alternative approaches and progressive new paths for welfare, the labour market and social rights.